Topical systems for the controlled release of antineoplastic Drugs: Oxidized Alginate-Gelatin Hydrogel/Unilamellar vesicles - Stagnoli, Soledad; Garro, Cintia; Ertekin, Özlem; Heid, Susanne; Seyferth, Stefan; Soria, Gastón; Mariano Correa, N.; Leal-Egaña, Aldo; Boccaccini, Aldo R. (Journal of Colloid and Interface Science, 2023)
The efficacy of chemotherapeutic procedures relies on delivering proper concentrations of anti-cancer drugs in the tumor surroundings, so as to prevent potential side effects on healthy tissues. Novel drug carrier platforms should not just be able to deliver anticancer molecules, but also allow for adjustements in the way these drugs are administered to the patients. We developed a system for delivering water-insoluble drugs, based on the use of 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC), or bis(2-ethylhexyl) sulfosuccinate benzyl-n-hexadecyldimethylammonium (BHD-AOT), embedded into oxidized alginate-gelatin (ADA/Gel) hydrogel, emulating a patch for topic applications. After being loaded with curcumin, cancer cells such as human colorectal adenocarcinoma (HCT116 and DLD-1) and melanoma cell lines (MEL501), and non-malignant cells such as mammary epithelial cell lines (NMuMG) and embryonal fibroblasts (NIH 3T3 or NEO cells) were analyzed for biocompatibility and cytotoxic effects. The results show that the proposed system can load comparatively higher concentrations of the drug (with respect to other nano/microcarriers in the literature), and that it can enhance the likelihood of the drug being uptaken by cancer cells instead of non-malignant cells. These assays were complemented by diffusion studies across the stratum corneum of rat skin, with the aim of determining the system's efficiency during topical application. Finally, the stability of the patch was tested after lyophilization to determine its potential pharmaceutical use. As a whole, the combined system represents a highly reliable and robust method for embedding and delivering complex insoluble chemotherapeutical molecules, and it is less invasive than other alternative methods in the literature.
CRIS-Team Scopus Importer:2022-10-14
Keywords: Controlled antineoplastic drug release; Hydrogel; Nanocarriers; Topical drug delivery system